Implementation and institutionalization of innovation and change in science education: the case of SEP. - Ntshoe, Isaac Mogapi (My University, 2014)
This investigation focuses on the evaluation of the vision, intention, policy implementation and institutionalization of curriculum development, innovation and change undertaken by the Science Education Project (SEP) from 1980 to 1995. The study yielded the following in relation to the research questions: It was found that SEP’s model and approaches to curriculum development and the usage of implementers were relevant to the conditions in South African education in the 1980s and 1990s. Further, that the introduction of innovation and change adopted by SEP (also known as the project) was effective, enabling and justified. It was also found that SEP had positively influenced the teaching and learning of science when it was still operating in the regions during the 1980s and the majority of the schools and teachers used the project’s materials and kits effectively in the late 1980s and 1990s. The vision, policy and implementation differed during the development, expansion and consolidation phases of the project. It was found that institutionalization (also called sustained implementation) of SEP’s innovation and change in education depended mainly on the support it received from the education administrators, the teachers and principals in the regions. The nature of the relationship between SEP and its other stakeholders was also a major determinant of the project’s success and a lack thereof contributed to its failure in other circumstances. This study contributes to knowledge relating to theories and models of curriculum development and educational innovation which suggest that: innovation is likely to be sustained when its clients become advocates of its work and implementation is likely to be sustained when teachers become advocates for its methodology. In particular,implementation is likely to be sustained when it is endorsed by persons working at different levels in the education systems. Further, the study shows that curriculum development is a dynamic process involving interaction between vision, intention and policy on the one hand and implementation or action on the other.